Brazilian fruit processing, wastes as a source of lipase and other biotechnological products: A review - Okino-Delgado, Clarissa H. [UNESP]; Prado, Débora Z. [UNESP]; Fleuri, Luciana F. [UNESP] (FapUNIFESP (SciELO), 2018)
The global food loss and waste is the most urgent research area in food science to attend the current demand for more sustainable and profitable processes. Along the productive chain about 1/3 of the food is lost or wasted, this number reaches 1/2 for fruit and vegetable production in developing countries. Brazil has been investing in researches aiming to turn its wastes into byproducts, as biomolecules of high value such as lipases. These enzymes are found in a high diversity of plant sources and their researches are covered by promising market growth expectations due to the current demand for biofuels and bio-transformed food. Thus, the aim of the present study is to discuss the potential of wastes generated by the Brazilian fruit processing to become a source of lipases, by the analysis of the most recent studies on fruit lipases, as well as the inclusion of this process in the biorefinery concept. According to this concept, different products can be obtained from the same raw material. Considering the confirmation of the presence of lipases on fruit wastes, the annual fruit production and the percentage of residues, the assessed data showed that wastes from the processing of orange, mango, papaya and palm are promising for lipase obtainment.
Keywords: Biorefinery; Fruit waste; Mango peel; Orange waste; Papaya peel and seed; Plant lipase